Us knows us in the UK: On director networks and CEO compensation - Renneboog, Luc; Zhao, Yang (Journal of Corporate Finance, 2011)
We analyze the relation between CEO compensation and networks of executive and non-executive directors for all listed UK companies over the period 1996–2007. We examine whether networks are built for reasons of information gathering or for the accumulation of managerial influence. Both indirect networks (enabling directors to collect information) and direct networks (leading to more managerial influence) enable the CEO to obtain higher compensation. Direct networks can harm the efficiency of the remuneration contracting in the sense that the performance sensitivity of compensation is then lower. We find that in companies with strong networks and hence busy boards the directors' monitoring effectiveness is reduced which leads to higher and less performance-sensitive CEO compensation. Our results suggest that it is important to have the ‘right’ type of network: some networks enable a firm to access valuable information whereas others can lead to strong managerial influence that may come at the detriment of the firm and its shareholders. We confirm that there are marked conflicts of interest when a CEO increases his influence by being a member of board committees (such as the remuneration committee) as we observe that his or her compensation is then significantly higher. We also find that hiring remuneration consultants with sizeable client networks also leads to higher CEO compensation especially for larger firms.